Processamento e caracterização de cerâmicas transparentes do sistema ferroelétrico PMN-PT dopado com lantânio - Badillo, Fernando Andrés Londoño (Universidade Federal de São Carlos, 2011)
In this work, one of the goals was the stabilization and/or optimization of the perovskita phase in the (Pb,La)(Mg1/3Nb2/3)O3+PbTiO3 (PLMN-PT) e Pb(Mg1/3Nb2/3)O3+PbTiO3+La2O3 (PMN-PT:La) powders in order to obtain ceramics with appropriate quality for optical applications. The stabilization of the system studied here was possible by the use of oxygen atmosphere in the powder calcinations process and densification process. Secundary phases, smaller to 5% and until 0% for the calcined powders and the densified pellets respectively were archived. After being given the best calcinations conditions, the pellets were conventionally and uniaxially hot pressing densified on oxygen atmosphere. For all the ceramics were performed structural, micro structural, and electrical characterizations. Comparisons between the systems studied (PLMN-PT and PMNPT: La) and between the densified processes used (conventionally and uniaxial hot pressing) were performed for all PT concentration. Relationship between vacancies and PT concentration were determined from measurements realized. Excellent properties were found for all the ceramics, as such, homogeneous microstructure, high density, free secondary phases and electrical properties as the reported in the literature. Light transmission (from visible to near infrared) was observed in ceramics obtained by uniaxil hot pressing. Electro-óptical characterization in function of frequency and temperature unprecedented were performed for all the transparent ceramics using the dynamic method Senarmont. Finally, electro-optics coefficient ideal for technological applications, this being, a clear sign of the excellent quality of the ceramics obtained in this work.
Keywords: Cerâmica; Cerâmicas transparentes; Relaxores ferroelétricos; Processamento cerâmico; CIENCIAS EXATAS E DA TERRA::FISICA